Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1980
DOI: 10.1029/gl007i010p00821
|View full text |Cite
|
Sign up to set email alerts
|

Four similar earthquakes in central California

Abstract: We study four ML ‐ 2.7 earthquakes on the San Andreas Fault in Central California. The first two events occurred within five minutes of each other in November 1978; the two events in January 1979 occurred within a nine hour period. The CALNET (USGS local array) seismograms of these four events display only some general similarity. However, when low ‐ pass filtered below 5 Hz, the four events have nearly identical seismograms. The similarity is even more striking in the pass‐band below 2 Hz. This suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
206
0
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(211 citation statements)
references
References 6 publications
4
206
0
1
Order By: Relevance
“…The same kind of phenomena as the clustering structure of microearthquakes have been observed in various regions as the existence of earthquake families with similar waveforms (e.g., HAMAGUCHI and HASEGAWA, 1975;GELLER and MUELLER, 1980;OKADA et al, 1981;PECHMANN and KANAMORI, 1982;URABE, 1982;TSUJIURA, 1983 a, b;MOTOYA, 1984;ITO, 1985). This study is the first, however, to reveal the fine structure of clusters and its influence on the fracture process of microearthquakes.…”
Section: Kasai Earthquake Groupmentioning
confidence: 90%
“…The same kind of phenomena as the clustering structure of microearthquakes have been observed in various regions as the existence of earthquake families with similar waveforms (e.g., HAMAGUCHI and HASEGAWA, 1975;GELLER and MUELLER, 1980;OKADA et al, 1981;PECHMANN and KANAMORI, 1982;URABE, 1982;TSUJIURA, 1983 a, b;MOTOYA, 1984;ITO, 1985). This study is the first, however, to reveal the fine structure of clusters and its influence on the fracture process of microearthquakes.…”
Section: Kasai Earthquake Groupmentioning
confidence: 90%
“…Hamaguchi and Hasegawa (1975) studied a large number of aftershocks of the 1968 Tokachi-Oki earthquake having similar wave forms, and concluded that these similar events occurred at approximately the same location under the same mechanical condition. Geller and Mueller (1980) ' CT (i, il found four small earthquakes with similar wave forms on the San Andreas Fault in Central California, and suggested that they may represent breakings of an asperity where stress is repeatedly concentrated and released.…”
Section: Discussionmentioning
confidence: 99%
“…The "multiplet blast" configuration was performed to record "multiplets" a term which refers, in classic seismology, to a group of seismic events showing the following characteristics (Geller and Mueller, 1980;Poupinet et al 1984;Lees 1998;Slunga et al, 1995;Moriya et al 2006;Gibowicz, 2006): similar wave form; different time origin; considered as the result of the relaxation of constrain of a single fracture or fault, similar source mechanisms; close location; different magnitude. The recorded data might indeed be used to test the capabilities of "relative" location algorithms compared to "absolute" and classical seismic location algorithms.…”
Section: Methodsmentioning
confidence: 99%